2014
DOI: 10.1111/hpb.12205
|View full text |Cite
|
Sign up to set email alerts
|

Anticoagulation policy after venous resection with a pancreatectomy: a systematic review

Abstract: There is significant heterogeneity in the use of anticoagulation after PV resection. Overall morbidity, mortality and EPVT in both groups were similar. EPVT has a high associated mortality. While we have been unable to demonstrate a benefit for anticoagulation, the incidence of EPVT is low in the absence of prosthetic grafts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(34 citation statements)
references
References 36 publications
2
30
2
Order By: Relevance
“…32 Finally, a systematic review of the available studies on PVR in the literature suggested prosthetic use during PVR to be a risk factor for PVR thrombosis, but this association was not statistically significant because of low numbers of patients. 36 We report the largest to date single-institution series of patients undergoing PVR during pancreas tumor resection and find that the overall PVR thrombosis rate is 13% and that reconstruction using a prosthetic graft is the main risk factor for PVR thrombosis. Patients who suffer PVR thrombosis are similar to those whose PVR stays patent in preoperative medical comorbidities and tumor characteristics, except for the higher prevalence of preoperative chemoradiation.…”
Section: Discussionmentioning
confidence: 89%
“…32 Finally, a systematic review of the available studies on PVR in the literature suggested prosthetic use during PVR to be a risk factor for PVR thrombosis, but this association was not statistically significant because of low numbers of patients. 36 We report the largest to date single-institution series of patients undergoing PVR during pancreas tumor resection and find that the overall PVR thrombosis rate is 13% and that reconstruction using a prosthetic graft is the main risk factor for PVR thrombosis. Patients who suffer PVR thrombosis are similar to those whose PVR stays patent in preoperative medical comorbidities and tumor characteristics, except for the higher prevalence of preoperative chemoradiation.…”
Section: Discussionmentioning
confidence: 89%
“…Therefore, routine post‐discharge subcutaneous heparin or Lovenox are infrequently used for prophylaxis. A recent meta‐analysis incorporating 13 studies and 361 patients with both benign and malignant disease (eight studies with an anticoagulation policy including aspiring, clopidogrel, heparin, or warfarin and five studies without an anticoagulation policy) found no difference in morbidity, mortality, or incidence of early portal vein thrombosis in pancreatic resections with venous reconstruction . Despite these data, given the technical complexity and heterogeneity of these operations and the consequences of thrombosis, it would be difficult to standardize practice in the absence of a randomized prospective trial.…”
Section: Discussionmentioning
confidence: 99%
“…Outside of the basic tenants to create a tension‐free anastomosis and optimize size match when interposition grafting is used, there is little in the literature relating the technical aspects and outcomes specific to each procedure. In addition, there is significant heterogeneity in the use of anticoagulation/antiplatelet therapy after PV/SMV reconstruction; use is at the discretion of the surgeon with no published guidelines that exist for the type or duration of anticoagulation/antiplatelet after venous reconstruction . The aim of this study was to define the rate and predictors of thrombosis after a pancreatectomy and concomitant venous resection/reconstruction, with particular attention to the influences of operative technique and post‐operative pharmacological management.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…12,60 No consensus or direct benefit of any prophylactic anticoagulation regimen has been found. 57,59,61 However, these data were derived primarily from high-volume centers and may not generalize to all hospitals. 5,8 The goal of venous resection during PD is to obtain grossly negative resection margins, although the reported effects on survival have been mixed.…”
Section: Venous Resectionmentioning
confidence: 99%